Genome-wide survey and characterization of transcription factors in the silk gland of the silkworm, Bombyx mori. - Yan Ma (Public Library of Science (PLoS), 2021)
Transcription factors (TFs) are key proteins that modulate gene transcription and thereby lead to changes in the gene expression profile and the subsequent alteration of cellular functions. In the silk gland (SG) of silkworm Bombyx mori, an important silk-producing insect, TFs are of vital importance in the regulation of silk protein synthesis in this organ. However, which TFs exist and express in the SG remains largely unknown. Here, we report the large-scale identification of TFs in the SG based on available full-length transcript sequences and the most recent version of silkworm genome data. In total, 348 candidate TFs were identified by strict filtration and were classified into 56 TF families. Chromosomal distribution, motif composition, and phylogenetic relationship analyses revealed the typical characteristics of these TFs. In addition, the expression patterns of 348 TFs in various tissues of B. mori, especially the SG of fourth-molt (4LM) and day-3 and day-4 fifth-instar (5L3D and 5L4D) larvae, were investigated based on public RNA-seq data and gene microarray data, followed by spatiotemporal verification of TF expression levels by quantitative real-time PCR (qRT-PCR). This report describes the first comprehensive analysis of TFs in the B. mori SG. The results can serve as a baseline for further studies of the roles of TFs in the B. mori SG.